2007
DOI: 10.7326/0003-4819-147-10-200711200-00185
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: The Comparative Effectiveness of Percutaneous Coronary Interventions and Coronary Artery Bypass Graft Surgery

Abstract: Compared with PCI, CABG was more effective in relieving angina and led to fewer repeated revascularizations but had a higher risk for procedural stroke. Survival to 10 years was similar for both procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
179
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(198 citation statements)
references
References 129 publications
7
179
0
12
Order By: Relevance
“…The meta-analysis showed that the rate of major adverse cardiac or cerebrovascular events was lower with CABG than with PCI and that patients who underwent CABG had fewer repeat revascularization procedures than patients who underwent PCI. After 5 years of follow-up, the meta-analysis did not show any significant differences in rates of survival between the CABG and PCI groups, 34 although other studies have shown differences in mortality. [10][11][12] Second, the use of medication differed between the groups in our study, reflecting variations in standard care of patients between the two treatment groups.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The meta-analysis showed that the rate of major adverse cardiac or cerebrovascular events was lower with CABG than with PCI and that patients who underwent CABG had fewer repeat revascularization procedures than patients who underwent PCI. After 5 years of follow-up, the meta-analysis did not show any significant differences in rates of survival between the CABG and PCI groups, 34 although other studies have shown differences in mortality. [10][11][12] Second, the use of medication differed between the groups in our study, reflecting variations in standard care of patients between the two treatment groups.…”
mentioning
confidence: 95%
“…The risk of repeat revascularization after PCI needs to be balanced against the invasiveness of CABG and the risk of stroke, as previously reported in a meta-analysis of 23 studies comparing CABG and PCI, in which procedure-related strokes were found to be more common after CABG (in 1.2% of patients, vs. 0.6% of those undergoing PCI; P<0.001), without a concomitant decrease in survival. 34 Recently, concern has been expressed about the possibility of an increased risk of late stent thrombosis with drug-eluting stents. In the SYNTAX trial, most cases of stent thrombosis occurred within 30 days after the procedure, and the 12-month rate of stent thrombosis in the PCI group was similar to the rate of symptomatic graft occlusion in the CABG group.…”
mentioning
confidence: 99%
“…Apesar da conhecida superioridade dos stents farmacológicos em relação aos stents convencionais em reduzir a necessidade de novas revascularizações da lesão-alvo, não foram utilizados tais stents neste estudo devido a sua não incorporação pelo SUS. Quando comparados a utilização dos stents convencionais e a cirurgia de revascularização miocárdica para tratamento da doença coronariana multiarterial, observou-se em metanálise recente, incluindo 23 ensaios randomizados com mais de 10.000 pacientes, que ao final de 5 anos de seguimento clínico não foi observada diferença significativa na mortalidade entre as duas terapêuticas, mas a cirúrgica forneceu maior durabilidade tardia da revascularização, com taxas menores de novos 16 18 . Quando a intervenção coronariana em multiarteriais foi realizada com stents farmacológicos e comparada aos resultados cirúrgicos, ocorreu uma grande redução da taxa de revascularização e, dependendo da complexidade das lesões, ainda mais favorável para a cirurgia 7 .…”
Section: Definiçõesunclassified
“…Balanced against these benefits is the observation that patients with DM who undergo revascularization experience less improvement in anginal symptoms compared to nondiabetics. 9 The BARI 2D trial was the first large randomized trial to enroll exclusively diabetic patients with CAD and stable angina. 10 This study demonstrated that an initial revascularization strategy plus optimal medical therapy yielded outcomes similar to optimal medical therapy with deferral of revascularization.…”
mentioning
confidence: 99%